Dr. Quinn medicine woman. The complete season four [videorecording (DVD)] - Bowman, Chuck; Seymour, Jane, 1951-; Lando, Joe, 1961-; Allen, Chad, 1974-; Bean, Orson (Fan favorites (CBS DVD (Firm)), 2013)
"In an age when women are expected to be seen but not heard, Dr. Michaela "Mike" Quinn is an independent spirit who forsakes her home in genteel Boston for the rough-and-tumble life of the frontier."--Boxed container.